The influence of circulation conditions on extreme precipitation totals over the territory of the Western Carpathians in the warm season - USTRNUL, Zbigniew; WYPYCH, Agnieszka; NEJEDLÍK, Pavol; MIKULOVÁ, Katarína (Contributions to Geophysics and Geodesy, 2023)
Based on data from a period of 72 years (1951–2022), the impact of atmospheric circulation on precipitation, which is usually the source of floods, was assessed for the area of the Western Carpathians. The analysis was performed for the season from April to October using daily rainfall totals originated from the E-OBS database and the calendar of circulation types according to Niedźwiedź’s classification. A very significant influence of cyclonic circulation with the airflow from the north and northeast on the amount of daily rainfall was found. This impact is generally visible throughout the entire area of interest, but the most spectacular in the Tatra region (Tatra Mountains and Low Tatras) and on the Czech-Polish-Slovak border (White Carpathians, Maple Mountains, Silesian Beskid). Simultaneously, the analysis showed quite large spatial variations in rainfall, which results from very complex local conditions, especially the orography.